A unifying mechanism for all high-temperature Heck reactions. The role of palladium colloids and anionic species - de Vries, Johannes G (Dalton transactions : an international journal of inorganic chemistry, 2006)
The Heck reaction has been the subject of intense investigation in the past decade. Many new types of catalysts have been developed in addition to the existing palladium/phosphine complexes. Prominent among these are palladacycles, pincers, several types of heterogeneous palladium catalysts, colloids and ligand-free palladium, usually in the form of Pd(OAc)2. Most of the newer types function only at higher temperatures, typically between 120 and 160 degrees C. It has been shown that irrespective of the catalyst precursor, none of these catalysts are stable at these high temperatures. They all have a tendency to form soluble palladium(0) colloids or nanoparticles, certainly with less reactive substrates such as aryl bromides or chlorides. The Heck reaction takes place by attack of the arylating agent on the palladium atoms in the outer rim of the nanoparticles. This leads to formation of monomeric or dimeric anionic palladium complexes that undergo the usual steps of the Heck mechanism as described by Amatore and Jutand.